THE RELATIONSHIP OF EDUCATION TO DANGEROUS SIGNS OF PREGNANCY TRIMESTER USING AUDIOVISUAL MEDIA TO LEVEL KNOWLEDGE OF PREGNANT WOMEN IN THE III TRIMESTER IN THE REGIONTELAGA DEWA HEALTH CENTER WORKBENGKULU CITY - dewi intan fitriani -; Novianti -; Deni Maryani -; Asmariyah -; Kurnia Dewiani - (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Backround : Danger signs of pregnancy are symptoms that indicate that the mother and baby are in danger. If the danger signs of pregnancy are not detected early, it can cause problems for the mother and fetus, resulting in a risk of death. Pregnant women's knowledge of the danger signs in pregnancy will minimize obstetric emergencies. Therefore, there is a need for education regarding this matter to increase knowledge among pregnant women. Method : This study employed a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 78 third trimester pregnant women selected through simple random sampling. Data collection involved pre-and post-intervention questionnaires, followed by univariate and bivariate analyse. Result : The results of the study showed that there was an increase in the knowledge of pregnant women in the third trimester after being given intervention using audiovisual media, previously there were (34.6%) respondents with good knowledge, (32.1%) with sufficient knowledge, (33.3%) with less knowledge and after being given the intervention it increased to (91.0%) respondents with good knowledge, and (9.0%) respondents with sufficient knowledge. The results of the bivariate test obtained a p-value of 0.001<0.005, which means that audiovisual media can be an effective medium in increasing the knowledge of third trimester pregnant women in the working area of the Telaga Dewa Community Health Center, Bengkulu City. Conclusion : Audiovisual media is effective in increasing pregnant women's knowledge about danger signs in the third trimester.